Stretch forming studies on a fibre metal laminate based on a self-reinforcing polypropylene composite - Sexton, A.; Cantwell, W.; Kalyanasundaram, S.
This paper investigates the room temperature formability of a fibre metal laminate system comprised of aluminium and a self-reinforcing polypropylene composite. Blanks of varying geometry were stretch formed over a hemispherical punch in a custom built stamping press. A real-time three-dimensional photogrammetric measuring system was used to acquire the evolution of surface strain and the strain at failure during forming. The results from this work illustrate that these advanced light weight material systems are amenable to mass production through stamp forming. A significant finding from this work is that these material systems can exhibit forming characteristics that are comparable and sometimes superior to metal forming
Keywords: FIBRE METAL LAMINATE; COMPOSITE STRUCTURES; EXPERIMENTAL MECHANICS; MANUFACTURING; 3D PHOTOGRAMMETRY